2006
DOI: 10.1007/s11121-006-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Youth Violence and Delinquency through a Universal School-Based Prevention Approach

Abstract: Abstract:Violence is an important public health problem among adolescents in the United States. Substance use and violence tend to co-occur among adolescents and appear to have similar etiologies. The present study examined the extent to which a comprehensive prevention approach targeting an array of individual-level risk and protective factors and previously found effective in preventing tobacco, alcohol, and illicit drug use is capable of decreasing violence and delinquency. Schools (N=41) were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
173
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(183 citation statements)
references
References 19 publications
3
173
1
6
Order By: Relevance
“…The last set of efficacious prevention programmes shown in table 2 addresses peer and individual risk factors and seek to change many outcomes, including drug use (Unplugged 65 and Life Skills Training 66,67 ), positive development (Positive Adolescent Training Through Holistic Social Programs 68,69 ), and risky sexual behaviours (Stepping Stones 70,75 and Sistering, Informing, Healing, Loving and Empowering 71 ). These prevention pro grammes have been assessed in several European countries, Hong Kong, South Africa, and the USA; they provide services directly to young people and target adolescent-onset risk factors.…”
Section: The Science Of Preventionmentioning
confidence: 99%
“…The last set of efficacious prevention programmes shown in table 2 addresses peer and individual risk factors and seek to change many outcomes, including drug use (Unplugged 65 and Life Skills Training 66,67 ), positive development (Positive Adolescent Training Through Holistic Social Programs 68,69 ), and risky sexual behaviours (Stepping Stones 70,75 and Sistering, Informing, Healing, Loving and Empowering 71 ). These prevention pro grammes have been assessed in several European countries, Hong Kong, South Africa, and the USA; they provide services directly to young people and target adolescent-onset risk factors.…”
Section: The Science Of Preventionmentioning
confidence: 99%
“…Promoting healthy practices among adolescent students and taking steps to protect them from health risks, in addition to formulating interventions and policies are critical for preventing health problems in adolescence and adulthood across countries (16).…”
Section: Introductionmentioning
confidence: 99%
“…Two previous quasi-experimental studies utilizing archival school-level data (Flay & Allred, 2003) reported beneficial effects on student achievement (e.g., math, reading, and science) and serious problem behaviours (e.g., suspensions and violence rates). As practitioners, policymakers and researchers have implemented programs and sought to raise academic achievement and to address negative behaviours among the youth, an increasing amount of evidence indicates a relationship among multiple behaviours (Botvin, Griffin, & Nichols, 2006;Catalano, Berglund, Ryan, Lonczak, & Hawkins, 2004;Flay, 2002). Several mechanisms involving multiple behaviours have been identified in improving student behaviour and performance (Domitrovich, Cortes, & Greenberg, 2007;Zins, Weissberg, Wang, & Walberg, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%